Implementasi PHBS dengan Dukungan Budaya 5R dalam Pengelolaan Lingkungan Bersih dan Sehat di Pondok Pesantren - Fany Apriliani; Henny Endah Anggraeni; Ika Resmeiliana; Yudith Vega Paramitadevi (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Islamic boarding schools are national education providers based on the Islamic curriculum and general education. Education and health must move in tandem so that students can study and do activities well. Problems that often occur in Islamic boarding schools are related to the application of clean and healthy living behavior (CHLB) and 5R culture. The purpose is to know the implementation of CHLB and 5R culture in women's boarding school Thoyyibah Al Islami, Bogor. The methods are training, questionnaires, observation, and designing guide booklets. The results show that the student’s understanding of the 5R culture and PHBS reached 89.5% and 98.3%, respectively. In its implementation, all students stated that they always use the toilet to bathe and defecate, use clean water, and do not smoke or consume drugs. Furthermore, 84.8% of students stated that they always clean their bedrooms and the environment regularly. They always wash their hands with soap and running water reaching 72.7%, and always dispose of garbage in the proper place reaching 69.7%. Meanwhile, students who always consume nutritious food and eradicate mosquitoes are relatively low, at 51.5% and 42.4%, respectively. The guide booklet is designed to increase participation in sustainably managing a clean and healthy environment.